Empowering Religious Educators in the Digital Age: An Evaluation of an ICT-Based Media Training Program - M. Imamul Muttaqin Arsandhi; Bahrul Ulum; Mufaizin Mufaizin; Junaidi Junaidi (Universitas Maritim AMNI Semarang, 2025)
This study evaluates a training program designed to enhance the competence of religious educators, known as